Analysis of Maximum Power Reduction Efficiency of Photovoltaic System at PT. Pertamina (Persero) RU III Plaju - Imas Ning Zhafarina; Tresna Dewi; R. Rusdianasari (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
The purpose of this research was to review the power output generated during the operation of the solar panels. Data that used to be taken of the Solar Power Plant or PLTS that operate PT. Pertamina (Persero) RU III Plaju observed data starting from January 2017 until December 2017 PLTS system installed in PT. Pertamina (Persero) RU III Plaju is a kind of photovoltaic grid connected (on grid). The results obtained that in manual calculations obtained fill factor of 0.7594 and output power of 250.884 Watts. Whereas the data in real time in the field fluctuating occurs at any time. This is because the weather was overcast, the lack of sunlight and shadow position (shading) that occurs due to the PLTS clouded by trees or buildings around also affects the results of the output voltage of the PLTS.